The Role Of Accounting Information Systems In Improving Business On Some Micro, Small And Medium Enterprises (Msmes) In Kendari, Indonesia - Tuti Dharmawati, Hasbudin, Arifuddin, Nurul Emil Safitri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the role of accounting information systems in improving business at several MSMEs in Kendari. This paper is a descriptive analysis with a qualitative approach. Data collection utilizes observation, interview and documentation techniques. The results indicate that the accounting information system can provide an overview of financial information for MSME players, especially in Kendari. Accounting information system allows MSME players to easily make the right business decisions which in result increases business of MSMEs in Kendari, Indonesia.